Development of Learning Tools Based on Mind Mapping Worksheet for Improving Stundents’ Creative Thinking Skills on Cell Material - Ainul Badriyah; Sri Poedjiastoeti; Yuliani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Life skills-based education is an important tool to face today's global demands, one of which is creative thinking skills. This study aims to determine the feasibility of learning tools based on mind mapping worksheet to practice creative thinking skills for class XI MIPA on cell material, which are viewed in terms of (1) validity, (2) practicality and (3) effectiveness. The learning tools developed are syllabus, lesson plans, LKDP and tests of creative thinking skills. The mind mapping worksheet that was trained included indicators of creative thinking skills, fluency, flexibility, originality and elaboration, which were tested on 23 students of Class XI MIPA SMA Al-Islam Krian. This study used a 4D design with one group pretest-posttest design, the data obtained were analyzed descriptively. The results of the validity of the device get mode 4 with a very valid category. The results of the practicality of the device were carried out with mode 4 in the very good category. The effectiveness of the device is based on the average N-gain score ranging from 0.5 to 0.92. The result of students' mastery of the concept of the material is 86.3 in the complete category. Students' responses to the four LKPD mind mapping developed were 81% in the positive category.